Effect of chopped co2 laser on enamel surface (Mustansiria Dental Journal, 2005)
This study aimed to assess the caries-preventive potential of various choppedCO2 laser parameters, and to explore the effect of the laser energy density on thecaries inhibition activity on enamel surface in vitro .Extracted human premolar teeth were irradiated with three various energydensities (25.47, 50.93, and 101.86) J/cm2, by changing the number of pulses, thepulse duration, and the spot diameter. The CO2 laser system emitted laser with6.01 um in wavelength and l0Hz repetition rate. All teeth were subjected to carieslikelesion tbrmation by 3.5 pH lactic acid for 2l days. The teeth after that were sectionedinto ground cross sections and the lesion depths were measured under a polarizingmicroscope .The result indicated that the chopped CO2 laser preventive treatments inhibitedcarieslike lesion progression up to 36%. This effect was improved with increased totalenergy density within the limits of the examined laser parameters